Welfare Gains of Aid Indexation in Small Open Economies - Dhasmana, Anubha (IMF Working Papers; Working Paper ;, 2008)
Foreign aid flows to poor, aid-dependent economies are highly volatile and pro-cyclical. Shortfalls in aid coincide with shortfalls in GDP and government revenues. This increases the consumption volatility in aid dependent countries, thereby causing substantial welfare losses. This paper finds that indexing aid flows to exogenous shocks like a change in the terms of trade can significantly improve the welfare of aid-dependent country by lowering its output and consumption volatility. Compared to the benchmark specification with stochastic aid flows, indexation of aid flows to terms of trade shocks can reduce the cost of business cycle fluctuations in the recipient country by four percent of permanent consumption. Moreover, use of indexed aid can allow donors to reduce the aid flows by three percent without lowering the level of welfare in the recipient country.